New Perspectives and Applications of Modern Control Theory In Honor of Alexander S. Poznyak (Springer International Publishing, 2018)
This edited monograph contains research contributions on a wide range of topics such as stochastic control systems, adaptive control, sliding mode control and parameter identification methods. The book also covers applications of robust and adaptice control to chemical and biotechnological systems. This collection of papers commemorates the 70th birthday of Dr. Alexander S. Poznyak. .